Analisis Pengaruh Tenaga Kerja dan PDB Terhadap Sektor Industri Manufaktur di Indonesia Tahun 2015-2020 - Nurfatimah, Siti; Yunani, Yunani; Dewi, Suci Mulya; Maulana, Rajendra Kimi; Desmawan, Deris (LPPM Universitas Labuhanbatu, 2024)
This research aims to analyse whether labour and Gross Domestic Product (GDP) have a positive influence on the manufacturing industry sector in Indonesia during the 2015-2020 period. The study utilises secondary data obtained from official publications by Statistics Indonesia (BPS), with the scope focusing on annual data. The approach used is a numerical method involving multiple linear regression analysis, where the predictor variables consist of labor and GDP, while the dependent variable is the manufacturing industry. The findings of the research indicate that, individually, there is a notable impact of labor on the manufacturing sector whereas GDP has no significant influence on the manufacturing industry. Overall, the independent variables studied were able to explain most of the variation in the performance of the manufacturing industry sector, although other influencing factors remain. These results carry significant consequences for decision-makers in formulating strategiesto maximize the contribution of labor and economic growth to the manufacturing industry.